Application of biofilm-chitin oral vaccine on streptococcosis infected red hybrid tilapia (Oreochromis sp.) - Kahieshesfandiari, Mahdi (2019)
Malaysia has started developing tilapia culture and has become one of the top countries in Asia. However, disease such as streptococcosis is one of the obstacles in the aquaculture industry. Two main and renowned species are Streptococcus agalactiae and Streptococcus iniae. For prevention of streptococcosis, the use of antibiotics is discouraged. Therefore, developing vaccines to prevent streptococcosis is highly recommended. In this study, a feed-based oral biofilm-chitin vaccine was developed and tested in red hybrid tilapia to prevent streptococcosis. For identification, the results confirmed ten isolates of S. agalactiae and three isolates of S. iniae by API20 strep and 16SrRNA gene sequencing. This was the first report on the isolation of S. iniae from red hybrid tilapia in Malaysia. The virulence of S. agalactiae and S. iniae was assessed by pathogenicity. The LD50 of S. agalactiae (MII) was determined to be 4.64 ×10⁶ CFU/ml, and S. iniae (TSK2) was 3.16 ×10⁵ CFU/ml. Clinical signs of streptococcosis were observed in infected fish such as erratic swimming, anorexia, loss of orientation, haemorrhage on the head and eye, exophthalmia, and corneal opacity. In this study, feed-based oral biofilm-chitin (10¹⁰ CFU/g) and feed-based oral free-cell (10¹⁰ CFU/ml) vaccines were tested to determine the antibody level of serum, mucus, and gut lavage against S. agalactiae infection in red hybrid tilapia. In the vaccinated groups, the antibody levels of the serum, mucus and gut lavage were significantly higher (P = 0.000) than those of the control group. the feed-based biofilm-chitin group for mucus (P= 0.039), serum (P = 0.042) and gut lavage (0.021) was significantly higher than those of the feed-based free-cell and control groups. For determining Relative Percentage Survival (RPS), the experimental groups were challenged intraperitoneally by 0.15 mL of live virulent S. agalactiae with a concentration of 109 CFU/ml. At 14 days post-challenge, the RPS values for the feed-based biofilm-chitin, feed-based free cell and control groups were 87, 57 and 0%, respectively. Total mortality was observed in control group due to streptococcosis. The obtained results revealed that the survival rate in the biofilm-vaccinated group was significantly higher (P = 0.000) than those in other groups, which lead to high efficacy of biofilm-chitin vaccine compared with the other groups. At the end of the experiment, the gut samples were subjected to histopathological test to evaluate the presence, size and number of lymphoid cells in GALT. As a result, the GALTs in the feed-based biofilm-vaccinated group were developed with higher intensity than those in the feed-based free- cell-vaccinated group. No GALT was observed in the control group. In addition, the size of GALTs and the number of lymphoid cells in the feed-based biofilm- vaccinated group were significantly higher (P = 0.000) than those in the feed- based free-cell-vaccinated group. In conclusion, this study revealed that the feed-based oral biofilm-chitin of S. agalactiae stimulated the systemic and mucosal immunity in red hybrid tilapia more than feed-based free-cell vaccine and non-vaccinated groups. Moreover, the protection of the feed-based oral biofilm-chitin of S. agalactiae was higher against S. agalactiae infection compared with the other groups. Thus, the feed- based oral biofilm-chitin can be a preferable candidate for dealing with S. agalactiae infection in red hybrid tilapia due to its efficacy, low cost and ease of usage.